2021
DOI: 10.1093/fampra/cmab067
|View full text |Cite
|
Sign up to set email alerts
|

The National Health Insurance System of Indonesia and primary care physicians’ job satisfaction: a prospective qualitative study

Abstract: Background The implementation of the National Health Insurance System (NHIS) in Indonesia has been changing the primary care physician (PCP) work condition and their job satisfaction. Objective This research aimed to explore the reasons behind PCPs’ satisfaction and dissatisfaction with job satisfaction’s aspect under the NHIS reform. Methods We conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…The main products of a hospital consist of human resources and equipment resources. Both resources should always be improved to instill the view that the hospital is good in the eyes of consumers [27].…”
Section: Discussionmentioning
confidence: 99%
“…The main products of a hospital consist of human resources and equipment resources. Both resources should always be improved to instill the view that the hospital is good in the eyes of consumers [27].…”
Section: Discussionmentioning
confidence: 99%
“…The government fully subsidizes the contribution from the state budget for the poor. In contrast, the government's contribution is partially supported (4%), and the rest is taken/deducted from their salary [ 55 – 57 ]. With a mechanism like this, the poor and government employees have a higher chance of having health insurance than other types of work or people with different socioeconomic statuses.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects include the referral system, NHI system health service standards, NHI system programs, performance evaluation and payment for performance, patient relations, and workload. 30 Meanwhile, a study in Yogyakarta also found that participants of the NHI revealed a lower level of trust in primary care physicians compared to physicians in hospital and specialist care. Access to care at primary care clinics is often complicated by long waiting times and short opening hours.…”
Section: Discussionmentioning
confidence: 99%